VD_FINDINFO HC / 2013 / 768 vom 11. Oktober 2013 - VD Tribunal cantonal (2013)
DIVORCE, MESURE PROVISIONNELLE, CONJOINT, OBLIGATION D'ENTRETIEN | 179 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)